Reassessing the Relationship between Marketing and Public Relations : New Perspectives from the Philosophy of Science and History of Thought - Dühring, Lisa (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2017)
Lisa Dühring reconstructs the relationship between public relations and marketing research on a metatheoretical level. She presents a concise systematization of the theoretical discourse in both disciplines since the beginning of the twentieth century by differentiating key phases of development and evaluating current research approaches. This study argues for a stronger connection of both disciplines and a better profiling within the mother disciplines of communication and business studies by fostering critical and interpretative approaches. This book is strongly recommended to everybody interested in the history and epistemology of marketing and public relations theory and the relationship between both fields. Contents - State of Research: The Academic Debate on the Relationship between Marketing and Public Relations - The Philosophy of the Social Sciences - The History Marketing Thought - The History of Public Relations Thought - New Perspectives on the Future Relationship between Marketing and Public Relations Target Groups Researchers, students and practitioners in the fields of marketing, marketing communications, corporate communications, communications management, public relations, strategic communications and organizational communication The Author Dr. Lisa Dühring is a former research associate at the Institute for Communication and Media Studies, Leipzig, Germany and currently works at the International Office at Leipzig University. Her research interests focus on the fields of critical PR and marketing studies, cross-disciplinary approaches, disciplinary development, and strategic communication.
Keywords: Social sciences.; Marketing.; Public relations.; Communication.; elektronické knihy; electronic books